Near-infrared-emitting five-monolayer thick copper-doped CdSe nanoplatelets - Sharma, Ashma (2020)
Doped nanocrystals are instrumental to the high-performance luminescent solar concentrators (LSCs) and the color conversion devices. Recently, copper (Cu)-doped three and four monolayer (ML) thick CdSe nanoplatelets (NPLs) have been shown superior to the existing Cu-doped quantum dots (QDs) for their use in LSCs. However, additional improvement in the LSC performance can be achieved by further redshifting the emission into the near-infrared (NIR) region of electromagnetic spectrum and increasing the absorbed portion of the solar irradiation. Cu-doping into higher thicknesses of these atomically flat NPLs (e.g., ≥5 ML) can achieve these overarching goals. However, addition of the dopant ions during the nucleation stage disturbs this high-temperature growth process and leads to multiple populations of NPLs and QDs. Here, by carefully controlling the precursor chemistry the successful doping of Cu in five ML thick NPLs by high-temperature nucleation doping method is demonstrated. The optimized synthesis method shows nearly pure population of doped five ML thick NPLs, which possess ≈150 nm Stokes-shifted NIR emission with high quantum yield of 65 ± 2%. Structural, elemental, and optical studies are conducted to confirm the successful doping and understand the detailed photophysics. Finally, these materials are tested experimentally and theoretically for their performance as promising LSC materials.